Model Pembelajaran Auditory Intellectualy Repetition terhadap Kemampuan Komunikasi Matematis Siswa - Ratu Mauladaniyati; Darojatun Nasihin (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2022)
This study aims to describe students' mathematical communication skills through the Auditory Interlectual Repetition learning model. The research method used in this research is descriptive qualitative. The subject in this study consisted of 3 students of class VIII SMP IT Mathla'un Nawakartika of each student's initial ability level. While data collection is done by test and interview method. Data analysis techniques, namely data reduction, data presentation, and verification. The results of the research show that: the mathematical communication skills of eighth grade students of SMP IT Mathla'un Nawakartika are in the medium category. High-ability students are able to master all indicators with a percentage of 100%. Moderately capable students are able to fulfill two indicators with a percentage of 75%. Low-ability students are not able to meet the three indicators of mathematical communication skills so that they get a percentage of 31.25%. The data is strengthened from the results of interviews that explore more in-depth information from the three research subjects. the average student meets the second indicator.